Refleksi Satu Dekade Undang-undang Pencegahan dan Pemberantasan Perusakan Hutan - Felix Aglen Ndaru; Pansos Sugiharto (Fakultas Hukum Universitas Islam Indonesia, 2024)
Forest destruction is a terrible problem which endangers forest sustainability in Indonesia. The government issued Law Number 18 of 2013 on Prevention and Eradication of Forest Destruction which entered its tenth year on August 6, 2023. This article presents a reflection on the 10-year implementation of the law. The study focuses on evaluating the Law in investigation aspect using normative legal research methods. Research data was obtained from secondary data sources and observations and analyzed descriptively using literature study method. The study identifies the legal instruments, the substances of the Law after the Job Creation Law, analysis of the application of the criminal provisions by the Investigators, and the challenges in utilizing the Law. The analysis recommends a mechanism for handing over casefiles from investigators to the prosecutor for further investigations as well as reviewing the time limitation criteria for law enforcement and expanding the definition of